T Cell Responses to Mycobacterial Glycolipids: On the Spectrum of “Innateness” - James, Charlotte A.; Seshadri, Chetan (Frontiers in Immunology, 2020)
Diseases due to mycobacteria, including tuberculosis, leprosy, and Buruli ulcer, rank among the top causes of death and disability worldwide. Animal studies have revealed the importance of T cells in controlling these infections. However, the specific antigens recognized by T cells that confer protective immunity and their associated functions remain to be definitively established. T cells that respond to mycobacterial peptide antigens exhibit classical features of adaptive immunity and have been well-studied in humans and animal models. Recently, innate-like T cells that recognize lipid and metabolite antigens have also been implicated. Specifically, T cells that recognize mycobacterial glycolipid antigens have been shown to confer protection to tuberculosis in animal models of the disease and share some biological characteristics with adaptive and innate-like T cells. Here, we review the existing data suggesting that glycolipid-specific T cells exist on a spectrum of “innateness”, which will influence how they can be leveraged to develop new diagnostics and vaccines for mycobacterial diseases.